1989
DOI: 10.1210/endo-125-4-1991
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone-Releasing Factor Production by Fetal Rat Cerebrocortical and Hypothalamic Cells in Primary Culture*

Abstract: Recent data from our laboratory and others have shown radioimmunoassayable GRF (IR-GRF) in the rat brain cortex. In the present study the ontogenesis of immunoreactive rat(r) GRF (IR-GRF) in long term dissociated fetal rat cerebrocortical and hypothalamic cell cultures and the regulation of its secretion by potassium depolarization and calcium channel-blocking agents were investigated. The chromatographic profiles of IR-rGRF from cell extracts were determined and compared with those from in vivo cerebrocortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…This inhibition was completely abolished with the blockade of SS with antiserum, thus indicating that the inhibitory effect was exerted by SS. This inhibition could be due to the fact that SS secretion by fetal hypothalamic cells in this in vitro model is 10 times greater than that of GHRH (11,14).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This inhibition was completely abolished with the blockade of SS with antiserum, thus indicating that the inhibitory effect was exerted by SS. This inhibition could be due to the fact that SS secretion by fetal hypothalamic cells in this in vitro model is 10 times greater than that of GHRH (11,14).…”
Section: Discussionmentioning
confidence: 86%
“…After 5 h of incubation, defined medium was replaced by Neurobasal medium. Experiments were performed after 15 days in vitro, which is when we have observed that high levels of SS secretion and the peak of GHRH secretion occur (11,14). Medium was changed every 3-4 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations